THE IMPORTANCE OF MODERN TECHNOLOGY IN EDUCATION AND LANGUAGE LEARNING - Khojamshukurova Dilfuza Qahhor kizi (International Engineering Journal For Research & Development, 2022)
This article reflects the role and relevance of modern technologies in education today, as well as the role of modern pedagogical tools in the promotion of foreign language learning.